Quantitative evaluation of OCT angiography images in healthy and glaucomatous subjects through a novel approach: exploring inter-image variability - Cassottana, Paola; Iester, Costanza; Bonzano, Laura; Traverso, Carlo E.; Iester, Michele (Eye (London), 2024)
Purpose This study aims to investigate inter-image intra-observer variability of macular, and optic disc (ONH) microvasculature measurements of glaucomatous and normal subjects using Swept-Source Optical Coherence Tomography Angiography (OCT-A) (OCT Topcon ImageNet 6; DRI OCT Triton, Topcon Corporation, JAPAN) - based imaging data analysis and processing with a newly made quantitative approach. Methods A total of 20 glaucomatous and 20 healthy eyes underwent three OCT-A scanning of the ONH and macula. Macular and papillary and peripapillary vascular networks were calculated. For each eye, eighteen scans were analyzed using a novel approach: custom MATLAB 2021b scripts were employed for imaging analyses. Grayscale distribution was performed using the histcounts MATLAB function with 51 bins. For all layers, the vascular layer coefficient of variation (vl CoV) of the three measures were performed. The vl CoV difference between the two groups was analyzed by Student t-test. Results In glaucomatous eyes, the vl CoV ranged from 4.49% to 8.54%, while in the control group from 3.58% to 8.32%. Both groups exhibited higher CoVs when assessing the optic disc. The papillary and macular microvasculature reproducibility was comparable between groups. Conclusions Utilizing Swept-Source OCT-A images our study has identified an easy and reproducible method that appears to be fast and can assist physicians in assessing macular and ONH perfusion with less inter-image variability, particularly in the 70 μm superficial area of the optic disc. The high reliability obtained suggested that this method could be useful as early clinical biomarker.